1994
DOI: 10.1111/j.1432-1033.1994.tb19048.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytosolic phospholipase A2 in human leukocytes by lipopolysaccharide

Abstract: Stimulation of peripheral blood leukocytes with lipopolysaccharide results in the synthesis of inflammatory cytokines including interleukin-1/3, interleukin-6, tumor necrosis factor-a and prostaglandin E, correlating with an increase in phospholipase A, activity. Mammalian cells contain several phospholipase A, isoforms including the 14-kDa secretory isoform and the more recently described high-molecular-mass cytosolic isoform. It is commonly believed that during inflammatory responses secretory phospholipase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
(13 reference statements)
1
14
0
Order By: Relevance
“…These data are consistent with previous studies, which reported induction of cPLA 2 by LPS in human leukocytes (44,45). Analysis of COX expression shows that resting BM-DC express only COX-1 and produce low levels of PGE 2 .…”
Section: Discussionsupporting
confidence: 83%
“…These data are consistent with previous studies, which reported induction of cPLA 2 by LPS in human leukocytes (44,45). Analysis of COX expression shows that resting BM-DC express only COX-1 and produce low levels of PGE 2 .…”
Section: Discussionsupporting
confidence: 83%
“…One of them is a 14 kDa secretory-type enzyme (sPLA # ) that requires high (probably millimolar) calcium concentrations for the catalysis [22][23][24]. The other one is a cytosolic PLA # (cPLA # ), with an apparent molecular mass of 85 kDa [25][26][27]. This enzyme is specific for AA in the sn-2 position of phospholipids and requires submicromolar Ca# + concentrations for translocation to membranes [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…a major lipid component of gramnegative bacterial cell walls, results in the synthesis of prostaglandin E2 and inflammatory cytokines including interleukin lp, interleukin-6 and tuinour necrosis factor-rx (Rodewald et al, 1994). In addition, LPS may prime neutrophils for an enhanced…”
mentioning
confidence: 99%
“…LPS also stimulates expression of the adhesion molecule p2 integrin (CDI 1 b/ CD18) in neutrophils (Lynn et al, 1991). The expression of CDI 1WCD18 in human neutrophils is regulated by phospholipase A, (PLA,: Jacobson and Schrier, 1993), and LPS triggers activation of the high-molecular-mass cytosolic isoform (Forehand et al, 1993;Rodewald et al, 1994). We sought to investigate the changes to the phospholipid composition of human neutrophils and their plasma membranes when stimulated with LPS, since the substrates for PLAL activity under these conditions have not been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation